Development of Personal Income Tax Achievement Using Skill Exercises within the Classroom in the Subject of Tax Law of Students in the Bachelor of Laws Program, School of Law and Politics, Suan Dusit University (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Objective of this research is as follows: 1) To study the effectiveness of the personal income tax skill exercise 2) to develop personal income tax achievement. Tax Law Course Of students in the Bachelor of Laws Program School of Law and Politics Suan Dusit University 3) To compare the learning achievement between the pre- and post-study programs of the Bachelor of Laws students who were taught using an in-class skill training exercise. The sample group is the 4th year students of the Bachelor of Laws in studying A1 34 people enrolled in the tax law course Semester 1, academic year 2019, which tools used in this research It is a skill practice exercise within the classroom. The researcher will use statistics, percentage (Percentage), Mean (Mean), Standard Deviation and T-test. 1. The efficiency of the personal income tax skill training form (E1)/(E2) was 56.32 / 86.76 2. The effectiveness of the personal income tax calculation    was 0.69, indicating that the students' knowledge increased by 69% from the States this gives students the skills to calculate personal income tax for better efficiency. 3. Academic achievement before and after study of students who study with the skill training form on the calculation of personal income tax There was a statistically significant difference at the 0.05 level of skill training, thus helping students develop their personal income tax education. It can be used as a guideline for the teaching development of the Bachelor of Laws program. School of Law and Politics Suan Dusit University to be more efficient..